POLITICAL BUZZERS FROM ISLAMIC LAW PERSPECTIVE AND ITS IMPACT ON INDONESIAN DEMOCRACY - Suud Sarim Karimullah; Arif Sugitanata; Aufa Islami (STAIN Sultan Abdurrahman Kepulauan Riau, 2022)
This research aims to stabilize conductivity in society so that this study will look at the impact of political buzzers on the development of ongoing democracy in Indonesia from the Islamic law perspective. In addition, this research not only explores political buzzers' problems clearly but also seeks to provide critical and reflective notes on previous studies. This study uses a qualitative approach with the type of research used is virtual ethnography because this study examines the phenomenon of society with virtual-based new media through the literature analysis method as a data collection technique by applying a critical paradigm which is analyzed with the analytical-descriptive pattern. Then the results of this study state that the phenomenon of the political buzzer is considered to have created a hegemony that the way of doing politics with the mechanism of attacking each other or provoking is the right way of politics. Therefore, the behaviour carried out by political buzzers has violated the provisions of Islamic law. In addition, the political buzzer also destroys the political ideology of future generations and the development of democracy in Indonesia.